Os primórdios do ensino de Ciências na modernidade amapaense (1943 – 1963) - Salcedo, Rocío Rubí Calla (2017)
This thesis, entitled "The Beginnings of Science Teaching in Amapa Modernity" (1947 - 1963), seeks to investigate how the process of introducing science occurred in the first public educational institution - Secondary School Amapaense College (Colégio Amapaense) and its relations with the modernity project In the Territory of Amapá. For that, the process of introduction of the Sciences through the curriculum of the Amapaense College and its relations with the modernity project in the Territory of Amapá was investigated. It was analyzed chronologically since the 40's, when the High School was created until 1963, when the Law on Guidelines and Bases of Education was published, giving new directions to Brazilian education. The beginning of the period under analysis occurs during the Government of President Getúlio Vargas, who chose the Brazilian Army captain, Janary Gentil Nunes, to direct the new territory of Amapá. Education was considered by this ruler as a powerful instrument for the modernization of the state. In order to investigate the introduction of the Sciences in the Territory of Amapá, we analyzed the speeches of the governors, the decrees of laws, the regulations, the newspapers of the time, the archive of the College and other factors related to education. With respect to the methodology of the research we follow the following steps: A) subjects and locus of the research: the research was based on three sources, namely: (1) historical documents of the Department of Public Instruction of the Federal Territory of Amapá; (2) in the acts of the government of the time; (3) in the archives of the Amapaense Gymnasium. B) Nature and method of research: Coming from the pedagogical field and entered into a Doctorate Program in Science Education, an interdisciplinary approach was sought to construct a work methodology contemplating both vocations (ours, as a researcher, and Of the Program as a research space). The curricular proposal with its official political context in itself was not the only interest of this research, the discourse on modernity in educational policy, was also welcomed by the administrative and educational agents of the past. It was possible to perceive the movement of introduction of the scientific disciplines in the curriculum of the Amapaense College in specific moments, attending to governmental discourses in force and in consonance with the greater project of introduction of the modern sciences in the Amazon and of all attitude of establishment of the new "modern" " in the region.